2020
DOI: 10.3389/fmicb.2020.00592
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Virulence Characterization, AMR Pattern and Genetic Relatedness of Vibrio parahaemolyticus Isolates From Retail Seafood of Kerala, India

Abstract: Narayanan et al. V. parahaemolyticus With Pathogenic Potential in Seafood The conventional methods used to identify the pathogenic V. parahaemolyticus would be good for clinical isolates, but a more elaborate method is recommended for the detection of tdh gene in environmental isolates. This is the first comprehensive study on pathogenic V. parahaemolyticus in Kerala, India and demonstrates for the first time, the isolation of potentially pathogenic V. parahaemolyticus, carrying tdh gene from seafood collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 57 publications
8
27
4
Order By: Relevance
“…Also, PCR-detected serotyping of 145 isolates for O-antigen by Xu et al (2016) revealed that serotypes with the exemption of O6, O9, and O7, were detected which was not in line with our study as O6 and O7 serotypes were detected in our study. Furthermore, our findings disagree with the study of Zhao et al (2011) that detected the O3 serotype as the most detected serotype from shellfish and the study of Narayanan et al (2020) that reported the prevalence O1 serotype in V. parahaemolyticus recovered from retail food and water samples. Location and serogroups did not correlate the phenotypic and/or genotypic profile of the V. parahaemolyticus in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also, PCR-detected serotyping of 145 isolates for O-antigen by Xu et al (2016) revealed that serotypes with the exemption of O6, O9, and O7, were detected which was not in line with our study as O6 and O7 serotypes were detected in our study. Furthermore, our findings disagree with the study of Zhao et al (2011) that detected the O3 serotype as the most detected serotype from shellfish and the study of Narayanan et al (2020) that reported the prevalence O1 serotype in V. parahaemolyticus recovered from retail food and water samples. Location and serogroups did not correlate the phenotypic and/or genotypic profile of the V. parahaemolyticus in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…The level of V. parahaemolyticus prevalence in this study appears to be lower when compared to the findings of Lee et al (2018) in which 69% (165/240) of the analyzed samples were known to be positive to V. parahaemolyticus (based on toxR PCR assay). Similarly, the study of Tan et al (2017) and Narayanan et al (2020) showed the prevalence of V. parahaemolyticus in samples analyzed as 79.5 and 90% respectively. Contrarily, the study of Yang et al (2017) demonstrated a lower level V. parahaemolyticus prevalence as 19.44% in tested samples.…”
Section: Discussionmentioning
confidence: 82%
“…The isolates were subjected to the antibiotic susceptibility test by the Kirby disc diffusion method [89] . This method has been employed in several studies investigating the antibiotic sensitivity in V. parahaemolyticus isolated from food samples [90,91] . All the isolates were revived in Tryptic Soy Broth (TSB) (HiMedia, India) supplemented with NaCl (2% w/v) and shaken at 37°C for 18 hours at 200 RPM.…”
Section: Antibiotic Susceptibility Testmentioning
confidence: 99%
“…Recently, in exception to the vibrios directly isolated from shrimp aquaculture system, reports of antibiotic‐resistant Vibrio sp. were identified from the commercial fish market samples (Kumar & Lalitha, 2013; Letchumanan et al, 2015; Madhusudana Rao & Surendran, 2010; Narayanan, Joseph, Peeralil, Koombankallil, et al, 2020; Narayanan, Joseph, Peeralil, Mothadaka, et al, 2020; Obaidat et al, 2017; Sperling et al, 2015; Wong et al, 2012; Yu et al, 2016).…”
Section: Amu Amr and Arg's In Vibriosmentioning
confidence: 99%